PKM Optimalisasi Sumber Belajar Rumah Tanam Herbal Medicine Berbasis Teknologi Iot Di Sekolah Alam Rumbai - Irma, Wirdati; Sunaryo, Sunaryo; Farida, Fitri; Purwanto, Hadi; Syurya, Rahmah Tika; Maltia, Laura Adza (LPPM UMRI, 2024)
Rumbai Nature School is located on Jl Budi Sari, Rumbai District, Pekanbaru City. Rumbai Nature School is located in the same area as the Muhammadiyah University of Riau, namely in Pekanbaru City. The IOT technology-based medicinal plant planting program is one form of learning resource that can be used as a means for children to learn about various types of medicinal plants. Medicinal plants or what are known as biopharmaceuticals are types of plants that have medicinal functions and properties and are used to cure or prevent various diseases. The method used in this service is designed so that activities can be carried out properly in order to optimize the IOT technology-based medicinal plant greenhouse at Rumbai Nature School. This service program is dedicated to providing educational guidance to improve students' knowledge about plants that have medicinal properties, both in terms of complaints about medicinal plants and regarding the use of medicinal plants. The presence of this service activity increases the awareness of school residents about how to utilize medicinal plants and utilize IoT technology to see the development and growth of ideal medicinal plants. Therefore, training is needed to introduce the use of medicinal plants and IoT technology